Asparagine deprivation mediated by Salmonella asparaginase causes suppression of activation‐induced T cell metabolic reprogramming. Issue 2 (23rd October 2015) - Torres, AnnMarie; Luke, Joanna D.; Kullas, Amy L.; Kapilashrami, Kanishk; Botbol, Yair; Koller, Antonius; Tonge, Peter J.; Chen, Emily I.; Macian, Fernando; van der Velden, Adrianus W. M.
Abstract : Asparagine deprivation causes inhibition of T cell activation characterized by the suppression of mTOR signaling, autophagy, Myc expression, and lactate secretion. Abstract : Salmonellae are pathogenic bacteria that induce immunosuppression by mechanisms that remain largely unknown. Previously, we showed that a putative type IIl ‐asparaginase produced by Salmonella Typhimurium inhibits T cell responses and mediates virulence in a murine model of infection. Here, we report that this putativel ‐asparaginase exhibitsl ‐asparagine hydrolase activity required for Salmonella Typhimurium to inhibit T cells. We show thatl ‐asparagine is a nutrient important for T cell activation and thatl ‐asparagine deprivation, such as that mediated by the Salmonella Typhimuriuml ‐asparaginase, causes suppression of activation‐induced mammalian target of rapamycin signaling, autophagy, Myc expression, andl ‐lactate secretion. We also show thatl ‐asparagine deprivation mediated by the Salmonella Typhimuriuml ‐asparaginase causes suppression of cellular processes and pathways involved in protein synthesis, metabolism, and immune response. Our results advance knowledge of a mechanism used by Salmonella Typhimurium to inhibit T cell responses and mediate virulence, and provide new insights into the prerequisites of T cell activation. We propose a model in whichl ‐asparagine deprivation inhibits T cell exit from quiescence by causing suppression of activation‐induced metabolic reprogramming.